Similarities of Thoughts between Allama Iqbal and Muhammad Akif Airsoye - Dr. Mohammad Kamran; Dr. Shabbir Hussain; Dr. Ayesha Maqsood; Dr. Farhat Jabeen Virk (Zaban-o-Adab, 2021)
Muhammad Akif and Allama Muhammad Iqbal were contemporaries. Allama Iqbal is Pakistan’s national poet and Muhammad Akif is Turkey’s national poet and the creator of country’s national anthem. Both Akif and Iqbal turned to poetry in search of an art form conducive for determinating social and political awareness. Perhaps one of the most significant contributions was their commitment to create awareness about the revival of Muslim Ummah. Keywords: Awareness, Ummah, Identity, Islam